The Dynamics and Vulnerability Degrees of Kampung Kemlayan’s Place Identity in Surakarta - Darumas Rismanu Andang Harjono; Bambang Hari Wibisono (Universitas Islam Sultan Agung Semarang, 2026)
This study examines the development and vulnerability of the place identity of Kampung Kemlayan in Surakarta, a settlement of royal artist servants that holds significant historical, socio-cultural, and symbolic values. The research aims to analyze the dynamics of identity-forming elements over the past two decades (2002–2025) and to assess their vulnerability to physical, social, and economic changes. A qualitative descriptive approach was employed, combining field observations, interviews, FGD, and questionnaires with secondary data drawn from historical maps, satellite imagery, and official documents. The findings reveal that the physical identity of the area has deteriorated due to the conversion of historic residences into shops, warehouses, or boarding houses, compounded by weak preservation regulations. The socio-cultural identity has declined as a result of regeneration of royal artist servants, social fragmentation, and decreasing youth participation. Collective memory and symbolic meaning have become increasingly fragmented under the pressures of gentrification and modernization, despite revitalization efforts through art studios and the designation of the area as a tourism village. The vulnerability assessment indicates high exposure and sensitivity, while the community’s adaptive capacity remains low to moderate. The study concludes that the identity of Kampung Kemlayan is highly vulnerable to the loss of historical and cultural integrity within the next 10–20 years unless policy interventions and stronger community participation are implemented. The implications highlight the urgency of designating historic residences as cultural heritage, revitalizing artistic traditions through youth engagement, and promoting participatory preservation strategies to ensure the sustainability of the area’s identity.Keywords: place identity, Kampung Kemlayan, Surakarta, vulnerability, urban heritage preservation, cultural sustainability. Penelitian ini membahas perkembangan dan tingkat kerentanan identitas Kampung Kemlayan di Kota Surakarta sebagai kampung abdi dalem seniman yang memiliki nilai sejarah, sosial-budaya, dan simbolik penting. Tujuan penelitian adalah untuk mengidentifikasi dinamika unsur pembentuk identitas dalam dua dekade terakhir (2002–2025) serta menilai tingkat kerentanannya terhadap perubahan fisik, sosial, dan ekonomi. Metode penelitian menggunakan pendekatan deskriptif kualitatif melalui observasi lapangan, wawancara, FGD, dan kuesioner yang dipadukan dengan data sekunder berupa peta historis, citra satelit, serta dokumen resmi. Hasil penelitian menunjukkan bahwa identitas fisik mengalami degradasi akibat alih fungsi bangunan bersejarah menjadi ruko, gudang, atau kos, serta lemahnya regulasi pelestarian. Identitas sosial-budaya menurun karena melemahnya regenerasi seni, fragmentasi sosial, dan menurunnya partisipasi generasi muda. Ingatan kolektif dan makna simbolik kawasan semakin terfragmentasi akibat gentrifikasi dan modernisasi, meskipun terdapat upaya revitalisasi melalui sanggar seni dan penetapan kampung wisata. Identifikasi tingkat kerentanan menunjukkan paparan dan kepekaan kawasan tergolong tinggi, sementara kapasitas adaptif masyarakat masih rendah hingga sedang. Kesimpulan utama menyatakan bahwa identitas Kampung Kemlayan sangat rentan terhadap hilangnya integritas sejarah dan budaya dalam 10–20 tahun mendatang apabila tidak ada intervensi kebijakan pelestarian dan penguatan partisipasi warga. Implikasi penelitian ini menegaskan pentingnya penetapan bangunan cagar budaya, revitalisasi tradisi seni berbasis generasi muda, serta strategi pelestarian partisipatif agar identitas kawasan tetap lestari dan berkelanjutan.Kata kunci: identitas tempat, Kampung Kemlayan, Surakarta, tingkat kerentanan, pelestarian warisan perkotaan, keberlanjutan budaya